Tiny patient, big challenge: decoding MDR Salmonella enterica Typhimurium ST29 with whole-genome sequencing - Faisal, Ummu Salamah; Zainulabid, Ummu Afeera; Kamarudin, A.Z.; Esa, Habib Abdul Hakim (Elsevier Ltd, 2025)
The emergence of multi-drug resistant Salmonella spp. (MDRS) is a growing global health concern, particularly in infants who are at heightened risk for severe infections due to their immature immune systems. This case highlights the utility of whole genome sequencing (WGS) in the management of invasive MDRS infections in a vulnerable paediatric patient.